(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
In 2005 the International Peace Bureau nominated the International Institute on Peace Education (IIPE) for the UNESCO Peace Education Prize. In the nomination it described the IIPE as “probably the most effective agent for the introduction of peace education to more educators than any other single non-governmental agency.”1 In a world where far too few opportunities exist for teacher training in peace education, for 26 years the IIPE has been providing unique short-term, residential, cooperative learning experiences in peace education. Held annually, the IIPE brings together educators and professionals from around the world to learn with and from each other in short-term learning communities that model principles of critical, participatory peace pedagogy. The IIPE has two primary goals: 1) to provide learning experiences and exposure to formal and non-formal educators to the content, pedagogy and teaching and learning methods of peace education as practiced by educators from around the world; and 2) to assist in the promotion and development of peace education in the host region and globally. This article will describe the pedagogy, structure and cooperative organizing model of the IIPE which work holistically together toward achieving these goals.